Electrochemical Behaviour of Thienyl-Fluorinated-β-Diketone Substrates and Their Conductivity in Solution - A. AL-ANBER, ZAID; A. AL-ANBER, MOHAMMED; AL-TAWEEL, SAMIR (Asian Journal of Chemistry, 2010)
The cyclic voltammetric investigations of π-conjugated thienyl fluorinated β-diketone (donor-acceptor moieties) substrates in the acetonitrile solution have been reported. We have performed cyclic voltammetry to show the influence of the fluorinated β-diketone substituent on the redox potential of thienyl unit. The cyclic voltammetry curves present one irreversible oxidation potential wave around + 1.88 V. This wave has reported for the thienyl unit. In addition, the curves have one-reversibly redox potential wave (E1/2), which is related for the fluorinated-β-diketone moiety. This redox wave is found between -1.10 to -1.53 V. Based on the geometrical structures substrates, these waves are discussed. The expected oligomers or dimer has been deposited as solid film. The electrical conduction of thienyl substrates has been evaluated in solution using conductivity. The influence of the substituents on the energy level and energy gap has been calculated using electronic spectra.